تمييز جنس المتكلم باعتماد العزوم السبعة لاشارة الكلام - د. خليل إبراهيم السيف; ميسون خضر النعيمي (PROSPECTIVE RESEARCHES, 2023)
In this research, a proposed approach has been adopted to represent the speech signal in two-dimensional arrays to make it suitable to evaluate the seven moments because the seven moments have stability in rotation, scaling and translation, which was adapted in many recognition fields. Many samples have been adopted for both male and female and a threshold value for both genders of the seven moments have been calculated after truncating the high frequencies from the speech signal by applying Fourier transformation, Then finding the correlation between the input samples and the threshold of both genders. The proposed algorithm contains two phases, in the first one the threshold values were built and the other phase works to test the gender of spooking person by evaluating the correlated distance between the speech parameters of the spooking person and the threshold values which were got in the first phase. The applied algorithm has given correct result up to 80% for male samples and 85% for female ones.